PSYCHOMETRIC PROPERTIES OF THE RELIGIOUS ATTITUDE SCALE (EAR) DURING THE COVID-19 PANDEMIC, LIMA, PERU - Tamayo-Toro, Mónica (2023)
The present study analyzes the psychometric properties of the Religious Attitude Scale of Orozco-Parra and Dominguez-Espinoza - 2014, adapted by Rivera-Encinas and Huarcaya-Victoria - 2019, finally composed of 14 items, with five Likert-type response alternatives. The participants were 137 students of different professional careers from private universities in Metropolitan Lima, Peru of both sexes, men and women, whose ages ranged between 18 and 30 years. Exploratory Factor Analysis suggested the existence of a single factor. Additionally, a Confirmatory Factor Analysis was carried out, obtaining adequate goodness-of-fit indices. Finally, reliability was analyzed using the omega coefficient, obtaining a value of 0.95, and using Cronbach's alpha coefficient, obtaining a value of 0.95. In conclusion, based on the Exploratory Factor Analysis and the Confirmatory Factor Analysis, adequate goodness-of-fit indices are observed, complying with the necessary validity aspects, as well as reliability, based on Cronbach's omega and alpha coefficients. Keywords: confirmatory factor analysis – exploratory factor analysis – reliability – religion – religious attitude – religious beliefs